Features Of Landscape Design For 9-Floor Residential Buildings - Saidov Abdumalik Abdulhaqovich , (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the peculiarity of planting trees and shrubs in the courtyard space of a 9-storey residential building in the second climatic zone of Uzbekistan. The nature and density of planting of green spaces at which the necessary light regime of the apartments is provided is determined. The possibility of creating interesting landscape compositions and achieving standardized values ​​of the density of green spaces according to SNK - 2.07.01.-03 (3-4 m2/ people), while ensuring the necessary light regime of apartments